A Typology of Digital Astroturfing - Kovic, Marko; Rauchfleisch, Adrian; Sele, Marc (AoIR Selected Papers of Internet Research, 2016)
In recent years, several instances of political actors creating fake grassroots activity on the Internet have been uncovered. We propose to call such fake online grassroots activity digital astroturfing. In this paper, we lay out a conceptual map of the phenomenon of digital astroturfing. To that end, we first define digital astroturfing as a form of manufactured, deceptive and strategic top-down activity on the Internet initiated by political actors that mimics bottom-up activity by autonomous individuals. Next, we explore a typology of digital astroturfing according to the dimensions of the target of digital astroturfing, the political actors who engage in digital astroturfing and the goals of the digital astroturfing activity. Following the discussion of our proposed typology, we introduce the concept of digital astroturfing repertoires, the possible combinations of tools, venues and actions used for digital astroturfing efforts. The main use of this conceptual study is to serve as a basis for future empirical work. Even though empirical research on digital astroturfing is inherently difficult since digital astroturfing is a clandestine activity, it is not impossible. We suggest some possible research strategies.